MAKNA KULTURAL DAN SOSIAL-EKONOMI TRADISI SYAWALAN - Anwar, Khoirul (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2013)
This article tries to uncover the cultural reason on Syawalan tradition in the village of Morodemak in Bonang, Demak. It also intends to reveal the meaning of the tradition for today’s society. Observations, interviews and examination of secondary data, can be conluded that the tradition of Syawalan in Morodemak is one of traditions that expresses the religious Javanese culture in coastal area. For Morodemak community, tradition of Syawalan is a form of gratitude to God Almighty for the gift of the abundance of seafood as well as an expression of prayer from dangerous things in life that can arise from the sea. Syawalan tradition also has the meaning of caring for nature, especially the sea as well as the meaning of cohesion and communality among fishing communities. In addition to the cultural meanings, traditions Syawalan also have economic and socio-cultural significance for the local governments and communities.***Tulisan ini berusaha untuk mengungkap nalar kebudayaan pada tradisi Syawalan di Desa Morodemak Bonang Demak. Selain itu juga bermaksud mengungkap makna tradisi tersebut bagi masyarakat saat ini. Hasil pengamatan, wawancara serta telaah terhadap data sekunder, dapat dijelaskan bahwa tradisi Syawalan di Morodemak merupakan salah satu tradisi masyarakat yang mengekspresikan kebudayaan masyarakat Jawa pesisiran yang religius. Bagi masyarakat Morodemak, tradisi Syawalan merupakan wujud rasa syukur pada Tuhan YME atas karunia melimpahnya hasil laut sekaligus ungkapan doa keselamatan dari segala mara-bahaya yang bisa timbul dari laut. Tradisi Syawalan juga memiliki makna kepedulian kepada alam, khususnya laut serta makna membangun kerukunan dan keguyuban di antara masyarakat nelayan. Selain makna-makna kultural tersebut, tradisi Syawalan juga memiliki makna ekonomis dan sosial budaya bagi pemerintah lokal dan masyarakat.